Analisis Pengetahuan Kepala Madrasah Tentang Sistem Informasi Dan Iklim Kerja Untuk Membentuk Efektivitas Kepemimpinan Di MTS Swasta Yaspen Muslim Pematang Tengah - Agnes Anggraini, Muhammad Saleh, Muamar Al Qadri (Pusdikra-Publishing.com, 2022)
The formulation of the problem in this study is: How is the effectiveness of the madrasa principal's leadership in managing information systems and work climates at Yaspen Muslim Islamic Private MTs Pematang Tengah. Another problem that can be found is that the creation of a good work climate in the madrasa environment has not been fulfilled. The principal applies an authoritarian system in leading the school so that a conducive school climate is not created. Leadership does not work effectively in madrasas. The impact is certainly very large for the education management that is carried out. The goals to be achieved will be difficult to achieve optimally because the existing systems are not well developed with one another. Innate will tend to be uncomfortable at work and the results will definitely not be effective. For this reason, it is necessary to build a good working relationship between the principal and the teacher. The conclusions in this study are that: An analysis of the madrasa principal's knowledge of information systems and work climate has a significant effect on the effectiveness of the madrasa principal's leadership. This is because if the principal does not have an understanding of information systems and the work climate, it can hinder the formation of leadership effectiveness. So, based on the results of observations and interviews conducted with resource persons, it can be concluded that the head of the madrasa has made a maximum contribution in shaping leadership effectiveness through knowledge of information systems and a good work climate.